Assessments of Different Antibiotic Regime in Treatment of Diarrhoea of Paediatric Patients. - Sudhir Shantilal Mavadia; Sachin Walchand Shah; Ravi Kishore Vankayala; Pankaj Kupwade (Asian Journal of Medical Research, 2019)
Background: One of the major health problem encountered worldwide among children is Diarrheal disorders. Fluid and electrolyte therapy is the mainstay of therapy. Hence; we planned the present study to assess the efficacy of different antibiotic regime in treatment of diarrhoea of paediatric patients. Subjects and Methods: A total of 40 paediatric patients with present of diarrhoea were included in the present study. All the patients were divided into two study groups with 20 patients in each group. Group 1 included subjects who were treated with ceftriaxone therapy while group2 included subjects who were treated with ciprofloxacin therapy. Microbial stool cultures were used as a standard for assessing the efficacy of both the antibiotic regimens. All the results were recorded in Microsoft excel sheet and were analysed by SPSS software.  Results: Mean age of the patients of group 1 and group 2 was 15.8 years and 14.9 years respectively. There were 12 males and 8 females in group 1 while there were 11 males and 9 females in group 2. Success rate among both the study groups was found to be 95 percent. Non- significant results were obtained while comparing the success rate of both the antibiotic treatment therapies. Conclusion: Both ceftriaxone and ciprofloxacin therapy are equally effective in treating diarrhoea in paediatric patients.